Dermatophytosis by Trichophyton verrucosum in domestic feline – case report (Research, Society and Development, 2022)
The present study aimed to report a case of dermatophytosis caused by Trichophyton verrucosum in a domestic feline. The patient was admitted to the University Veterinary Hospital of the Federal University of West Bahia, with dermatological complaints. On physical examination, alopecic lesions with an erythematous, hyperpigmented appearance and the presence of papules were noted, which were distributed throughout the body, with a greater predominance in the thoracic limbs, ventral region and head. Dermatological samples were collected from different areas of the body with lesions, which were sent for mycological culture and research for ectoparasites at the Laboratory of Clinical Analysis and Veterinary Microbiology of the same institution. The fungal examination showed the growth of colonies with a prominent center and flat periphery with salmon coloring and a subtly granular texture, demonstrating on microscopy hyaline septate fungal filaments, the presence of few piriform to ovoid shaped microconidia, in addition to several chlamydospores and hyphae with engorgement. terminal, compatible with “pearl chains”, confirming a case of dermatophytosis by T. verrucosum. The literature approaches this fungus as a cause of disease in cattle and other ruminants, however there is still little information about its distribution and epidemiology in felines in Brazil, revealing the need for epidemiological studies in the area. It is concluded, therefore, that T. verrucosum infection in felines should be considered as a differential diagnosis of other dermatological conditions in the small animal clinic.